Discrimination of Bamboo Species by Shape Descriptor of Culm Sheath - Singh, Krishna; Gupta, Indra; Gupta, Sangeeta (Indian Forester, 2013)
Bamboo has been widely used as building material throughout the world. There are about 1200-1500 species of bamboos. The bamboo culm sheath shapes provide valuable data in identification of bamboo species. Automated recognition of bamboo has not yet been well established mainly due to lack of research in this area, non-availability and difficulty in obtaining the database. Using digital image processing and pattern recognition techniques, a supervised classification procedure of three different bamboo species has been developed. In the proposed work, an automated bamboo species recognition system based on shape features of bamboo culm sheath has been developed by calculating the Legendre moment. A confusion matrix is created to quantify the class wise and the classifier accuracy. The system can eliminate the need for laborious human recognition method requiring a plant taxonomist. The results obtained shows considerable recognition accuracy proving that the techniques used is suitable to be implemented for commercial purposes.